Prediction of Anastomotic Leakage After Laparoscopic Low Anterior Resection in Male Rectal Cancer by Pelvic Measurement in Magnetic Resonance Imaging. Issue 1 (February 2017) - Tsuruta, Atsushi; Tashiro, Jo; Ishii, Toshimasa; Oka, Yasuo; Suzuki, Asami; Kondo, Hiroka; Yamaguchi, Shigeki
Abstract : Objective: Anastomotic leakage after laparoscopic low anterior resection in male rectal cancer patients with a narrow pelvis cannot be easily resolved. The objective of this study is to assess numerical information of narrow pelvis and to determine whether prediction of morbidity can be possible. Methods: Retrospective medical record review was performed. From July 2007 to January 2013, 43 consecutive male patients with low rectal cancer who underwent laparoscopic low anterior resection were divided into the anastomotic leakage–negative group and anastomotic leakage–positive group. Eleven anatomic parameters were measured from preoperative magnetic resonance imaging of pelvis and a new index called "pelvic index" was calculated. Results: The pelvic index (difference between the interspinous distance and the diameter of the mesorectum divided by the depth of the cavity of the lesser pelvis) in the leakage-positive group was significantly smaller than that in the negative group ( P =0.038). Comparison between those 2 groups at the border of the cut-off value of the pelvic index (13.0) showed a significant difference. Conclusions: Preoperative assessment by the pelvic index can predict the narrow pelvis and risk of anastomotic leakage.